Pseudotargeted metabolomics revealed the adaptive mechanism of Draba oreades Schrenk at high altitude - Lei, Ling; Yuan, Xuefeng; Fu, Keyi; Chen, Yuan; Lu, Yijun; Shou, Na; Wu, Dandan; Chen, Xi; Shi, Jian; Zhang, Minjuan; Chen, Zhe; Shi, Zunji (Frontiers in Plant Science, 2022)
Strong ultraviolet radiation and low temperature environment on Gangshika Mountain, located in the eastern part of the Qilian Mountains in Qinghai Province, can force plants to produce some special secondary metabolites for resisting severe environmental stress. However, the adaptive mechanism of Draba oreades Schrenk at high altitude are still unclear. In the current study, Draba oreades Schrenk from the Gangshika Mountain at altitudes of 3800 m, 4000 m and 4200 m were collected for comprehensive metabolic evaluation using pseudotargeted metabolomics method. Through KEGG pathway enrichment analysis, we found that phenylpropanoid biosynthesis, phenylalanine, tyrosine and tryptophan biosynthesis and phenylalanine metabolism related to the biosynthesis of flavonoids were up-regulated in the high-altitude group, which may enhance the environmental adaptability to strong ultraviolet intensity and low temperature stress in high altitude areas. By TopFc20 distribution diagram, the content of flavonoids gradually increased with the elevation of altitude, mainly including apigenin, luteolin, quercetin, hesperidin, kaempferol and their derivatives. Based on the random forest model, 10 important metabolites were identified as potential biomarkers. L-phenylalanine, L-histidine, naringenin-7-O-Rutinoside-4’-O-glucoside and apigenin related to the flavonoids biosynthesis and plant disease resistance were increased with the elevation of altitude. This study provided important insights for the adaptive mechanism of Draba oreades Schrenk at high altitude by pseudotargeted metabolomics.